Dermoscopic Features of Benign Pigmented Skin Lesions on Face - Othman, Awat Hassan; Saeed, Mohammed Yousif (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Benign pigmented skin lesions (BPSL) on the face, including melanocytic nevi, lentigines, freckles, lichen planus pigmentosus, pigmented seborrheic keratosis, pigmented actinic keratosis, lichenoid keratosis, hypertrophic lichen planus, and melasma. Dermoscopy is used to aid the diagnosis and to help exclude malignant skin lesions. Aims: To recognize benign features of pigmented lesions using dermoscopy as a noninvasive procedure, reduce the rate of biopsy as invasive as much as possible, and be more familiar with benign dermoscopic features of benign pigmented lesions and differentiate them from pigmented malignant lesions. Methods: This observational cross-sectional study was done in Sulaimaniyah Dermatology Teaching Center from 1st July 2021 to 30th May 2022. One-hundred fifty patients with benign face pigmented lesions were enrolled. Clinical and dermoscopic assessments of each lesion were performed using Molescope TM II. Results: Melanocytic lesions were the most prevalent type of benign pigmented lesions on the face in 97 patients (64%), and the most frequent dermoscopic features include homogenous brown pigmentation, typical pigmented network, and regular distributed dots and globules. Hyperkeratotic lesions were the second most common benign and premalignant lesions in 40 patients (27.3%), and among them, pigmented seborrhiek keratosis was the most prevalent lesions in 20 patients (13.3%), while the most abundant dermoscopic findings were homogenous brown pigmentation in 100% (20 patients), followed by 95% (19 patients) for each milia likecyst, comedo like opening, and mouth border. Inflammatory lesions were the least prevalent pigmented lesions in 13 patients (8.7%), and melasma was the most common inflammatory lesion in 11 patients (7.3%). At the same time, most observed dermoscopic findings were homogenous brown pigmentation, pseudo network, dots/globules, and telangiectasia in 100% (11 patients). Conclusion: Dermoscopy was the definite tool for diagnosing BPSL, locating on the face and differentiating them from pigmented malignant lesions.
Keywords: dermoscopy; benign pigmented skin lesions; noninvasive procedure; cross sectional study